Citizens of the World, A History and Sociology of the Baha'is from a Globalisation Perspective. - Margit Warburg (Numen Book Series, 2006)
Citizens of the World deals with the Baha'is and their religion. While covering the historical development in sufficient detail to serve as a general monograph on Baha'i, emphasis is laid on examining contemporary Baha'i, with the Danish Baha'i community as a recurrent case. The book discusses Baha'i religious texts, rituals, economy, everyday life, demographic development, mission strategies, leadership, and international activism in analyses based on primary material, such as interview studies among the Baha'is, fieldwork data from the Baha'i World Centre in Israel, and field trips around the world. The approach is a combination of history of religions and sociology of religion within a theoretical framework of religion and globalisation. Several general topics in the study of new religions are covered. The book contributes to the theoretical study of globalisation by proposing a new model for analysing globalisation and transnational religions.